Antithrombotic Effects of Combined PAR (Protease-Activated Receptor)-4 Antagonism and Factor Xa Inhibition. Issue 11 (November 2020) - Meah, Mohammed N.; Raftis, Jennifer; Wilson, Simon J.; Perera, Vidya; Garonzik, Samira M.; Murthy, Bindu; Everlof, J. Gerry; Aronson, Ronald; Luettgen, Joseph; Newby, David E.
Abstract : Objective: PAR (protease-activated receptor)-4 antagonism has antiplatelet effects under conditions of high shear stress. We aimed to establish whether PAR4 antagonism had additive antithrombotic activity in the presence of factor Xa inhibition in an ex vivo model of acute arterial injury. Approach and Results: Fifteen healthy volunteers (29±6 years, 7 women) completed a phase zero double-blind randomized controlled crossover trial. Ex vivo platelet activation, platelet aggregation, and thrombus formation were measured following blood perfusion of low shear and high shear stress chambers. Upstream of the chambers, extracorporeal blood was admixed with (1) vehicle, (2) low-dose apixaban (20 ng/mL), (3) high-dose apixaban (80 ng/mL), (4) BMS-986141 (400 ng/mL), (5) BMS-968141 and low-dose apixaban, or (6) BMS-968141 and high-dose apixaban in 6 sequential studies performed in random order. Compared with vehicle, BMS-986141 demonstrated selective inhibition of PAR4-AP (agonist peptide)–stimulated platelet aggregation, platelet-monocyte aggregates, and P-selectin expression ( P ⩽0.01 for all). Total thrombus area was reduced under both low shear and high shear stress conditions for all drug infusions ( P <0.0001 for all versus vehicle). BMS-968141 reduced total (⩽44.4%) and platelet-rich (⩽39.3%) thrombus area, whereas apixaban reduced total (⩽42.9%) and fibrin-rich (⩽31.6%) thrombus area. Combination of BMS-986141 with apixaban caused a further modest reduction in total thrombus area (9.6%–12.4%), especially under conditions of high shear stress ( P ⩽0.027). Conclusions: In the presence of factor Xa inhibition, PAR4 antagonism with BMS-986141 further reduces thrombus formation, especially under conditions of high shear stress. This suggests the potential for additive efficacy of combination PAR4 antagonism and factor Xa inhibition in the prevention of atherothrombotic events. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.